2018
DOI: 10.1161/circulationaha.117.031907
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Cost-Effectiveness of Fractional Flow Reserve–Guided Percutaneous Coronary Intervention in Patients With Stable Coronary Artery Disease

Abstract: BACKGROUND: Previous studies found that percutaneous coronary intervention (PCI) does not improve outcome compared with medical therapy (MT) in patients with stable coronary artery disease, but PCI was guided by angiography alone. FAME 2 trial (Fractional Flow Reserve Versus Angiography for Multivessel Evaluation) compared PCI guided by fractional flow reserve with best MT in patients with stable coronary artery disease to assess clinical outcomes and cost-effectiveness. METHODS:A total of 888 patients with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(132 citation statements)
references
References 14 publications
4
123
0
5
Order By: Relevance
“…DEFER, FAME, and FAME 2 established that in SIHD, FFR‐guided PCI is superior to conservative therapy. PCI of lesions with reduced FFR improves long‐term outcome and is economically advantageous.…”
Section: Clinical Utility Of Translesional Measurementsmentioning
confidence: 99%
“…DEFER, FAME, and FAME 2 established that in SIHD, FFR‐guided PCI is superior to conservative therapy. PCI of lesions with reduced FFR improves long‐term outcome and is economically advantageous.…”
Section: Clinical Utility Of Translesional Measurementsmentioning
confidence: 99%
“…The 3‐year follow up of the FAME 2 trial, which prospectively randomized patients with at least one vessel coronary artery disease and an abnormal FFR (≤0.80) to PCI versus medical therapy, found FFR guided PCI to be associated with a lower MACCE (10.1% vs 22.0%, P < 0.0001). The reduction was primarily driven by a lower rate of urgent revascularization, decreased angina, and improved quality of life without a difference in death and MI.…”
Section: Coronary Physiology and Imagingmentioning
confidence: 99%
“…However, it is more specific and masking of one ischaemic area by another, more severely ischaemic, zone is avoided since every artery or segment is analysed separately [20,21]. In addition, FFR-guided revascularisation has been shown to be cost-effective [22]. A recent study has shown that FFR can reliably assess IRA infarct-related artery, PCI percutaneous coronary intervention, STEMI ST-elevation myocardial infarction, TAVI transcatheter aortic valve implantation, TIMI thrombolysis in myocardial infarction, QCA quantitative coronary angiography the haemodynamic severity of non-culprit coronary artery stenosis during the acute phase of STEMI [23].…”
Section: Introductionmentioning
confidence: 99%